The Disclosure of Leniency Statements and Other Evidence under Directive 2014/104/EU: An Undue Prominence of Public Enforcement? - Claudia Massa (Market and Competition Law Review)
Directive 2014/104/EU contains detailed provisions related to the disclosure of evidence in actions for damages before national courts that seek to strike a balance between a claimant’s right to access evidence in support of its private damages claim and the protection of leniency programmes, which are some of the main tools of public antitrust enforcement. Articles 5 to 8 of the Directive create a “microsystem” of the law of the evidences, which is highly specialised and based on the central role of the judge and on the principle that private enforcement must not compromise public enforcement. The Directive tackles the information asymmetry that characterises competition law litigation by acknowledging the right for a claimant “to obtain the disclosure of evidence relevant to their claim, without it being necessary for them to specify individual items of evidence”. However, the obtainment of the disclosure of evidence is circumscribed by a number of conditions and exceptions. The Directive creates three lists of documents that are characterised by a different level of protection: the black list, the grey list and the white list. After giving an overview of all these provisions, the article will focus on the disclosure of leniency statements and settlement submissions, by analysing the case law of the ECJ before and after the entry into force of the Directive. It will be found out that while the Court has always been cautious, by affirming that it is necessary to weigh up, on a case-by-case basis, the respective interests in favour of disclosure of such documents and those in favour of their protection, the European Legislator preferred to unconditionally protect the efficiency of leniency and settlement programmes to the detriment of parties that suffered a harm, which have to find any possible way to support their damage claim in a context in which the information asymmetry and the difficulty of the factual and economic analysis are evident. It seems that, with Article 6(6), the European Legislator did not succeed in its goal of making it easier for victims of antitrust violations to claim compensation from the offender, which is the general aim of the Directive. In fact, not having the possibility to have access to leniency statements or settlement submissions in stand-alone actions, it is highly difficult to prove that they suffered harm. Therefore, victims can only wait until the competition authority adopts a final infringement decision in order to start a probably successful follow-on action. Overall, all provisions on disclosure of documents contained in the Directive contribute to make a big step forward in the private enforcement sector, except for the provisions of Article 6(6), which could have probably been less rigid. In fact, while the rule on the right to obtain the disclosure of evidence, together with the provisions on disclosure of documents contained in the grey list and in the white list, strike a fair balance between public and private enforcement and facilitate victims of antitrust violations in bringing actions for damages, the same thing cannot be affirmed for provisions on disclosure of documents contained in the black list.